THE ROLE OF PHYSICAL EDUCATION AND STEPS IN THE FORMATION OF SPIRITUAL APPEARANCE IN PEOPLE - Otabek Amonturdiyev Qurbonovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the role of physical education and sports in shaping the spiritual and moral image of students. The impact of physical education and sports on the human psyche, spirituality and morality is analyzed.